Hubungan Pendidikan yang Ditempuh dan Jenis Sekolah terhadap Perilaku Merokok pada Remaja Laki-Laki Usia SMA/Sederajat (15-18 Tahun) di Surabaya - Rosaline Dinda Arista; Kurnia Dwi Artanti (Universitas Airlangga, 2023)
Background: In Indonesia, smoking is one of the problems that has not been solved at this time. Smoking can cause various diseases, such as cancer, hypertension, and others. Adolescence is a time when a person has a deep curiosity, so there is a sense of curiosity, so it is not surprising if found many teenagers who have smoking behavior. It was found that many teenage boys in Surabaya as the capital of East Java Province have smoking behavior. Objectives: This study aims to analyze the relationship between education taken and school type to smoking behavior among male school adolescents in senior high school (age 15-18 years) in Surabaya Methods: This research was an observational quantitative analytic study with a cross-sectional design by distributing online questionnaires via a g-form link. The sample taken in this study used a non-random sampling method with an accidental sampling technique. The number of samples is 369 respondents. Results: From the analysis of the chi-square test that had been carried out, the results show a significant relationship between education taken and smoking behavior among male school adolescents in senior high school (age 15-18 years) in Surabaya (p value = 0.000). Then, there was no significant relationship between the type of school and smoking behavior among male school adolescents in senior high school (age 15-18 years) in Surabaya (p value = 0.652). Conclusion: Education taken is a factor related to smoking behavior among male school adolescents in senior high school (age 15-18 years) in Surabaya.